Updated estimates of excess total mortality in Italy during the circulation of the BA.2 and BA.4-5 Omicron variants: April-July 2022 - Alicandro, Gianfranco; Gerli, Alberto Giovanni; Remuzzi, Giuseppe; Centanni, Stefano; La Vecchia, Carlo (La Medicina del Lavoro, 2022)
Background: The impact of new lineages and sub-lineages of Omicron on total and excess mortality is largely unknown. This study aims to provide estimates of excess mortality during the circulation of the Omicron variant in Italy updated to July 2022. Methods: Over-dispersed Poisson regression models, fitted separately for men and women, on 2011-2019 mortality data were used to estimate the expected number of deaths during the Covid-19 pandemic. The excess deaths were then obtained by the difference between observed and expected deaths and computed at all ages and at working ages (25-64 years). Results: Between April and June 2022, we estimated 9,631 excess deaths (+6.3%) at all ages (4,400 in April, 3,369 in May, 1,862 in June) and 12,090 in July 2022 (+23.4%). At working ages, the excess was 763 (+4.9%) in April-June 2022 and 679 (+13.0%) in July 2022. Conclusions: Excess total mortality persisted during the circulation of different lineages and sub-lineages of the Omicron variant in Italy. This excess was not limited to the elderly population but involved also working age individuals, though the absolute number of deaths was small. The substantial excess found in July 2022 is, however, largely attributable to high temperatures. At the end of the year, this may translate into 30 to 35,000 excess deaths, i.e. over 5% excess mortality. This reversed the long-term trend toward increasing life expectancy, with the relative implications in social security and retirement schemes.